2018
DOI: 10.1111/cen.13836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium citrate vs calcium carbonate on elevated parathyroid hormone after Roux‐en‐Y gastric bypass. A double‐blinded, randomized trial

Abstract: Increasing the dose of calcium supplementation in RYGB operated patients with slightly elevated PTH levels does not normalize PTH levels, regardless of the type of supplement. Our results do not support recommending supplementation with calcium citrate over calcium carbonate in RYGB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Calcium carbonate was used as calcium supplement. Calcium carbonate is best absorbed in an acidic environment, and absorption is possibly lower after RYGB (42,43), although other studies have shown no difference between calcium carbonate and calcium citrate supplementation on PTH and BMD after RYGB (44,45). Generalizability of our results is limited, as we only included Caucasian women.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium carbonate was used as calcium supplement. Calcium carbonate is best absorbed in an acidic environment, and absorption is possibly lower after RYGB (42,43), although other studies have shown no difference between calcium carbonate and calcium citrate supplementation on PTH and BMD after RYGB (44,45). Generalizability of our results is limited, as we only included Caucasian women.…”
Section: Discussionmentioning
confidence: 99%
“…PTH levels and bone turnover markers can stay elevated years after both sleeve gastrectomy and RYGB [ 39 ]. Treatment includes calcium and vitamin D. Calcium as citrate may be more easily absorbed in this setting [ 40 ]; however, it may be difficult to normalize PTH levels in these patients with calcium citrate or carbonate [ 41 ]. Interestingly, there have been reports of PHPT with hypercalcemia after RYBG [ 42 ].…”
Section: Casesmentioning
confidence: 99%
“…1600mg daily) composed of citrate or carbonate forms, did not show any significant difference in PTH and vitamin D levels. Noteworthy, the citrate form was associated with reduced bone turnover markers suggesting less bone resorption [54], yet BMD was not assessed.…”
Section: Effects Of Supplementation On Vitamin Status and Clinical Oumentioning
confidence: 99%